First Principle Studies to Tailor Graphene Through Synergistic Effect as a Highly Efficient Electrocatalyst for Oxygen Evolution Reaction. Issue 11 (14th May 2021) - Riyaz, Mohd; Gupta, Shuchi; Goel, Neetu
Abstract: The Oxygen Evolution Reaction (OER) is one of the major roadblocks for electrocatalytic oxidation of water (water splitting) and for designing efficient metal‐air batteries. Herein, we present a comprehensive study to design graphene based efficient electrocatalyst, modified by doping with main group elements Al, Si, P, S and co‐doping with B and N, for OER using DFT computations. Four elementary steps in the OER reaction have been traced, free energy change for each elementary step was calculated considering thermodynamic corrections. Out of all the doped models, S doped graphene shows maximum efficiency that was further enhanced by adjusting the concentration of codopants B and N around the active dopant site. Our results show that synergy between codopants B and N and dopant S atom leads to high electrocatalytic efficiency of modified graphene towards OER and brings down the overpotential to as low as 0.44 V. Abstract : Co‐doped graphene as electrocatalyst : Catalytic cycle of oxygen evolution reaction over S‐doped graphene is illustrated. The model catalyst is tuned, by co‐doping with different concentrations of B and N‐atom at various positions, to minimize the reaction overpotential. The synergy between the dopants minimize the OER overpotential to as low as 0.44 V.